2022
DOI: 10.22541/au.165035703.39925793/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Infant with TAFRO Syndrome: Case Report and Review of the Literature

Abstract: A rare lymphoproliferative disorder involving thrombocytopenia (T), anasarca (A), fever (F), reticulin fibrosis (R), and organomegaly (O), so called TAFRO syndrome, was first reported in 2010.1 Considered a variant of idiopathic multicentric Castleman’s disease, the recent discovery and rarity of this syndrome poses significant challenges to diagnosis and management. In this case report, we review the youngest patient to be reported in the literature with TAFRO syndrome. We highlight the patient’s diagnosis, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the anasarca persisted; therefore, tacrolimus was administered, which proved to be effective. The tacrolimus was continued without adverse events and the glucocorticoids were successfully tapered [55]. This case suggests that tacrolimus may also be effective and well tolerated in infants with TAFRO syndrome.…”
Section: Rituximabmentioning
confidence: 81%
See 2 more Smart Citations
“…However, the anasarca persisted; therefore, tacrolimus was administered, which proved to be effective. The tacrolimus was continued without adverse events and the glucocorticoids were successfully tapered [55]. This case suggests that tacrolimus may also be effective and well tolerated in infants with TAFRO syndrome.…”
Section: Rituximabmentioning
confidence: 81%
“…Although cyclosporine A has been widely used in the treatment of TAFRO syndrome [13], information regarding cases treated using tacrolimus remains limited. To the best of our knowledge, only four studies have reported the use of tacrolimus treatment for TAFRO syndrome [20,38,55,56] (Table 2), excluding one in which the duration of tacrolimus use was markedly short to evaluate its efficacy [33]. Among these studies, we first described two cases of TAFRO syndrome that were successfully treated using tacrolimus [20].…”
Section: Rituximabmentioning
confidence: 99%
See 1 more Smart Citation